2011
DOI: 10.1371/journal.pone.0014507
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Function Is Required for Secretion of DAF-28/Insulin in C. elegans

Abstract: While insulin signaling has been extensively studied in Caenorhabditis elegans in the context of ageing and stress response, less is known about the factors underlying the secretion of insulin ligands upstream of the insulin receptor. Activation of the receptor governs the decision whether to progress through the reproductive lifecycle or to arrest growth and enter hibernation. We find that animals with reduced levels of the mitochondrial outer membrane translocase homologue TOMM-40 arrest growth as larvae and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 53 publications
5
19
0
Order By: Relevance
“…The effect of loss of PRDX-2 on DAF-28::GFP secretion is comparable to the reported effects of RNAi targeting asna-1 or mitochondrial components, which have previously been shown to be important for insulin secretion (Figs2 and S1) (Kao et al ., 2007; Billing et al ., 2011). However, in contrast to loss of asna-1 or mitochondrial function, for example tomm-20 , there is no larval arrest/constitutive dauer phenotype associated with loss of PRDX-2 function.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of loss of PRDX-2 on DAF-28::GFP secretion is comparable to the reported effects of RNAi targeting asna-1 or mitochondrial components, which have previously been shown to be important for insulin secretion (Figs2 and S1) (Kao et al ., 2007; Billing et al ., 2011). However, in contrast to loss of asna-1 or mitochondrial function, for example tomm-20 , there is no larval arrest/constitutive dauer phenotype associated with loss of PRDX-2 function.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we did not observe GFP expression in the germline, most likely because of transgene silencing (Kelly et al 1997). Finally, insulins are secreted peptides that may act cellnon-autonomously (Billing et al 2011;Bai et al 2012). Nonetheless, we provide both a first comprehensive data set as well as a set of transgenic strains, both of which enable future studies of the functional dynamics of the entire C. elegans insulin gene family in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, reducing TOM40 levels in C. elegans retarded growth [41], as did introducing assembly-defective TOM40 mutations in N. crassa [38]. …”
Section: Introductionmentioning
confidence: 99%
“…The C. elegans RNAi screen showed that reduced TOMM40 levels arrested growth between the 1st and 3rd larval stages; TOMM40 knock-out animals exhibited a phenotype similar to the knock-downs [41]. In neither case were there detectable developmental defects or structural or functional defects in the worms’ feeding apparatus [41], indicating the animals ability to feed was intact and TOMM40 per se was required for continual growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation